TINGKAT KEPUASAN PENGGUNA LAYANAN TERHADAP PROSES PENDAFTARAN RAWAT INAP DI RUMAH SAKIT UMUM DAERAH ABDOEL WAHAB SJAHRANIE SAMARINDA - Fatmawati Bakri Noor; Galih Persadha; Suwandi Suwandi; Robi'atul Adawiyah (Politeknik Unggulan Kalimantan, 2025)
Health services are a fundamental need that plays a crucial role in supporting the quality of life. One of the key indicators in evaluating the success of hospital services is patient satisfaction. As service users, patients expect to receive quality, comprehensive care aligned with their rights. This study uses a quantitative method with a descriptive approach to assess patient satisfaction with the inpatient registration services at Abdoel Wahab Sjahranie Hospital, Samarinda. A total of 92 respondents were selected using a random sampling technique, and data were gathered through a structured questionnaire. The findings indicate that patient expectations are met across five satisfaction dimensions: tangibles (80%), reliability (95.5%), responsiveness (98.3%), assurance (98.5%), and empathy (98.5%). These results suggest that inpatient registration services have succeeded in meeting patient expectations. Patient satisfaction should be prioritized as it directly influences service quality and the hospital’s reputation. In conclusion, the majority of patients expressed satisfaction with the inpatient registration process at Abdoel Wahab Sjahranie Hospital, Samarinda.